2002
DOI: 10.1152/ajpcell.00478.2001
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of Na+-K+-Clcotransporter to high-[K+]o- induced swelling and EAA release in astrocytes

Abstract: We hypothesized that high extracellular K(+) concentration ([K(+)](o))-mediated stimulation of Na(+)-K(+)-Cl(-) cotransporter isoform 1 (NKCC1) may result in a net gain of K(+) and Cl(-) and thus lead to high-[K(+)](o)-induced swelling and glutamate release. In the current study, relative cell volume changes were determined in astrocytes. Under 75 mM [K(+)](o,) astrocytes swelled by 20.2 +/- 4.9%. This high-[K(+)](o)-mediated swelling was abolished by the NKCC1 inhibitor bumetanide (10 microM, 1.0 +/- 3.1%; P … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
135
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(145 citation statements)
references
References 41 publications
10
135
0
Order By: Relevance
“…When K-gluconate replaced intracellular Cs-glutamate, a small outward current was recorded (5). The addition of 10 mM BAPTA in the pipette (same conditions as in 3) inhibited the inward current (6). When 100 M NPPB was added to the bath (same conditions as in 3), the inward current was inhibited other amino acids, such as leucine, phenylalanine, and tyrosine, were not released (Fig.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…When K-gluconate replaced intracellular Cs-glutamate, a small outward current was recorded (5). The addition of 10 mM BAPTA in the pipette (same conditions as in 3) inhibited the inward current (6). When 100 M NPPB was added to the bath (same conditions as in 3), the inward current was inhibited other amino acids, such as leucine, phenylalanine, and tyrosine, were not released (Fig.…”
Section: Discussionmentioning
confidence: 86%
“…Astrocytes possess multiple mechanisms for several key functions. For example, the important task of K ϩ buffering is undertaken by several K ϩ channels expressed by astrocytes, including KIR4.1 and rSlo K(Ca) (5), but also by the K ϩ -Na ϩ -Cl Ϫ cotransporter (6).…”
mentioning
confidence: 99%
“…Genetic ablation of NKCC1, as well as its block by bumetanide,17 causes a decrease in intracellular Cl − in hypoxic neurons145 and blocks Na + -and Cl − -mediated cell swelling in astrocytes. 101,142,143 In vivo studies have shown that intracerebral bumetanide administered via a microdialysis probe, either prior to or during ischemia/hypoxia insult caused by temporary MCA occlusion, is neuroprotective, ameliorates brain damage, and reduces brain edema in rat focal ischemia,141,172,173 reinforcing the in vitro data. Focal cerebral ischemia in rats results in elevated NKCC1 protein levels in the ipsilateral cortex and striatum.…”
Section: The Nkcc Channelmentioning
confidence: 82%
“…In a rat model of cerebral ischemia, NKCC1 transcripts and protein are significantly upregulated in cortical neurons, as well as in whole brain lysates [54,55]. These changes may occur in ischemic conditions secondary to elevated extracellular potassium and glutamate levels, substances known to stimulate NKCC1 activity in neurons and neuroglia [18,56,57]. Cytokines may also be involved in ischemiainduced upregulation of NKCC1, with interleukin-6 shown to activate NKCC1 in capillaries [58].…”
Section: Nkcc1mentioning
confidence: 99%